The Reasons Behind Sustainable Product Purchases. What Affects Consumers More – Cognition or Emotions? - Dagytė-Kavoliūnė, Gintarė (Vilnius University Proceedings, 2023)
More and more scientists are pointing to the need for sustainable consumption research in order to find an effective way to promote sustainable products among consumers. Scientists note that sustainable consumption is often illusory. The research shows that consumers have a positive attitude towards sustainable products, but that does not always correlate with actual consumers’ purchasing behaviour. Accordingly, the question arises of how to promote consumers to buy sustainable products. Recent theories in the field of decision-making, such as Dual Processing theories, place increasing importance on emotional response. The aim of this article is to investigate the emotional and cognitive factors that affect consumers’ intentions to buy sustainable products. Based on theoretical aspects, a model that examines the intersection between the emotional and cognitive responses on consumers’ intentions to buy sustainable products is proposed.